Registration of 'Devote' soft white winter wheat. Issue 1 (3rd November 2020) - Carter, A.H.; Balow, K.A.; Shelton, G.B.; Burke, A.B.; Hagemeyer, K.E.; Stowe, A.; Worapong, J.; Higginbotham, R.W.; Chen, X.M.; Engle, D.A.; Murray, T.D.; Morris, C.F.
Abstract: The development of soft white winter (SWW) wheat ( Triticum aestivum L.) cultivars requires numerous traits to be successfully commercialized in the low‐ to intermediate‐rainfall (<400‐mm average annual precipitation) wheat production regions of the state of Washington, including winterhardiness, high grain volume weight, acceptable end‐use quality, and resistance to stripe rust, Fusarium crown rot (FCR), strawbreaker foot rot, and snow mold. Two essential traits for the low‐ to intermediate‐rainfall production regions of the state are emergence from deep planting and high grain yield under low annual rainfall conditions. 'Devote' (Reg. no. CV‐1170, PI 693628) SWW wheat was developed and released in March 2019 by the Agricultural Research Center of Washington State University. Devote is a semi‐dwarf cultivar adapted for the low‐ to intermediate‐rainfall wheat production regions of the state, emerges well under deep planting conditions, and is winter hardy. Devote has high‐temperature adult‐plant resistance to the stripe rust pathogen, carries the Pch1 gene for strawbreaker foot rot, is resistant to FCR and tolerant to snow mold, is intermediate in height, has late‐season maturity, and has high grain volume weight and grain yield. The end‐use quality properties of Devote are acceptable for cookie, cake, and cracker production.